The horrible peace : British veterans and the end of the Napoleonic Wars - Wilson, Evan, 1984- (Veterans (University of Massachusetts Press), 2023)
"Few battles in world history provide a cleaner dividing line than Waterloo: before, there was Napoleon; after, there was the Pax Britannica. While Waterloo marked France's defeat and Britain's ascendance as an imperial power, the war was far from over for many soldiers and sailors, who were forced to contend with the lasting effects of battlefield trauma, the realities of an impossibly tight labor market, and growing social unrest. The Horrible Peace details a story of distress and discontent, of victory complicated by volcanism, and of the challenges facing Britain at the beginning of its victorious century. Examining the process of demobilization and its consequences for British society, Evan Wilson draws on archival research and veterans' memoirs to tell the story of this period through the experiences of veterans who struggled to reintegrate and soldiers and sailors who remained in service as Britain attempted to defend and expand the empire. Veterans were indeed central to Britain's experience of peace, as they took to the streets to protest the government's indifference to widespread unemployment and misery. The fighting did not stop at Waterloo"--